Análisis de clúster para la clasificación de pacientes atendidos en consulta de infertilidad. - Rodríguez-Monteagudo, Mabel A.; Avello-Martínez, Raidell; Avello-Rodríguez, Amanda (Revista Cubana de Informática Médica)
Introduction: Spermogram is the clinical examination that provides the broadest view of the male reproductive capacity and includes a large number of parameters to be interpreted. Objective: To characterize the male patients attended at the Consultation for the Care of the Infertile Couple in Cienfuegos through a cluster analysis of spermogram variables. Methods: A cross-sectional study of the spermograms performed on patients seen at the Consultation for the Care of the Infertile Couple in Cienfuegos Municipality was carried out in the period 2019 - 2020. The sample consisted of 128 patients. Two clusters were created using the hierarchical k-means algorithm, executed by the R statistical language. Results: The values of the spermogram showed very wide ranges in all the variables. The first group, with more favorable values in the spermogram parameters, included 82.8% of the patients. There were significant differences between the two clutters for all the variables, except leukocytes; the ones that were most defining for their formation were: vitality, rapid mobility, total mobility, and concentration. Conclusions: It was possible to group the patients from the infertility consultation in Cienfuegos into two clusters with significant differences in most of the spermogram parameters, which made it possible to characterize this population globally. These clusters could later be used to create a complementary tool for the individual diagnosis of these patients.